Children and Terrorism: Human Rights for Indonesian Cubs of Caliphate - Indah Gitaningrum (Jurnal Penelitian, 2021)
This paper aims to analyze the intertwined relations among the children's involvement in terror activities and the freedom of religion or belief. The new pattern of terrorism in Indonesia occurs within the involvement of family on several terror bombings including one of the massive tragedies in Surabaya during 2018. As the largest home of Muslim population in the world, Indonesia has struggled with radicalization issues but the latest horrifying phenomenon is the terrorism involving children in the activities. It raises the notion of human rights protection for children not only among their basic human rights but also their freedom of religion or belief. By using literature research method and interview with BRSAMPK Handayani Jakarta, it concludes that all children, including the child of terrorist, should be considered as victim of terrorism. Their presence in terror actions is the result of ideological indoctrination that violating children’s human rights including freedom of religion or belief.